2021
DOI: 10.33425/2689-1093.1036
|View full text |Cite
|
Sign up to set email alerts
|

The Brachial Plexus: More and More Variations

Abstract: The brachial plexus is so variable that most of dissected cases will show some form of anatomical variations. In the same person, the right and left sides are not the same. This study was done to identify the variations of the brachial plexus and highlight their clinical significance. The materials of this study included 10 cadavers dissected on both sides to find out the variations of the different parts of the plexus. Variations were found in 85% of cases. Variations included all stages of the plexus. Phren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
1
0
1
Order By: Relevance
“…Emamhadi et al (2016) observed 64 brachial plexuses and found, in one case, the origin of an upper subscapular nerve to arise from the superior trunk of the brachial plexus [ 15 ]. Yet another case reported a unique variation in which the posterior cord was replaced by the posterior division of the upper trunk and gave rise to the upper subscapular nerve and axillary nerve, and continued as the radial nerve [ 16 ]. None of these studies, or cases, describe any arterial variation coexisting with the aberrant branching patterns of the upper subscapular nerve.…”
Section: Discussionmentioning
confidence: 99%
“…Emamhadi et al (2016) observed 64 brachial plexuses and found, in one case, the origin of an upper subscapular nerve to arise from the superior trunk of the brachial plexus [ 15 ]. Yet another case reported a unique variation in which the posterior cord was replaced by the posterior division of the upper trunk and gave rise to the upper subscapular nerve and axillary nerve, and continued as the radial nerve [ 16 ]. None of these studies, or cases, describe any arterial variation coexisting with the aberrant branching patterns of the upper subscapular nerve.…”
Section: Discussionmentioning
confidence: 99%
“…Esse nervo possui origem principal dos ramos ventrais do nervo espinhal C4, com contribuições dos ramos ventrais de C3 e C5, em que o ramo C5 coincide também com uma das raízes do plexo braquial (CANGIANI; REZENDE; GIANCOLINETO, 2008). Todavia, a origem deste nervo pode variar, sendo, por vezes, mais um ramo colateral do plexo braquial(ELZAWAWY, 2021).Em um estudo realizado pela Universidade de São Paulo (USP) no plexo braquial de 27 cadáveres (totalizando 54 plexos braquiais) divididos por sexo e raça, foi constado, em 20% dos casos, a presença do nervo frênico tendo total origem no plexo braquial, especificamente na sua raiz em C5 -encontrado majoritariamente em cadáveres masculinos e da raça branca(FAZAN et al, 2003). bloqueado, o paciente terá dispneia, com dificuldades para realizar os movimentos respiratórios, devido ao comprometimento da contração do m. diafragma(HORTENSE et al, 2010).→ Curso a conclusão obtida é que essa variação deve ter sua devida atenção e cuidado, pois torna o indivíduo vulnerável a lesões nervosas em cirurgias de rotina no pescoço.→ Anastomose de Riché-CannieuA anastomose de Riché-Cannieu (ARC) consiste em uma conexão que pode existir entre o ramo profundo do nervo ulnar e ramos do nervo mediano na mão, especificamente na região tenar (BOLAND; KRISHNAN;KIERNAN, 2007).…”
unclassified